COVID-19 Pandemic: The Existing Challenges and Available Solution; Evidence from a Systematic Review (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Coronavirus disease (COVID-19) is presently the most important topic worldwide. However, no vaccine or specific anti-viral treatment for the disease has been shown to be effective. In this emergency, identifying risk factors, preventive measures and estimating challenges which control available drug options for COVID-19 are key to mitigating the severity of the pandemic until specific drugs or vaccines become available. Therefore, this study aims to identify possible factors which affect these drug options. This study searched PubMed database using necessary Boolean operators from December 31st to March 31st 2020 in order to identify common risk factors, preventive measures, information regarding control challenges & evidence on the available drug options against COVID-19. Risk factors were found to be human-animal interactions, males, aged peopleand people with co-morbidity. Furthermore, protective factors comprised of personal hygiene etiquette maintenance, rapid identification, isolation and informing (3I tools) of the COVID-19 cases and media coverage on COVID-19. Till date, anti-viral drugs like remdesivir, chloroquine, lopinavir/ritonavir and traditional Chinese medicine (TCM) are available options to fight against COVID-19. More research is needed to determine other how to control the disease until specific treatment options are available as well as risk factors, and preventive measures.